Development of a nomogram based on body composition and tumor burden indicators to predict lymph node metastasis in patients with T1 esophageal squamous cell carcinoma - Qingwen Liu; Junxi Hu; Lin Liu; Wenbo He; Jiaqi Hou; Yusheng Shu; Xiaolin Wang (BMC Cancer)
Abstract Background Treatment strategies for patients with early esophageal cancer are diverse, and lymph node metastasis (LNM) remains a critical determinant in therapeutic decision-making and prognosis. However, current methods for predicting LNM in early esophageal cancer are limited. Aim To evaluate the impact of body composition parameters on LNM in early esophageal squamous cell carcinoma (ESCC) and to develop a nomogram based on body composition and tumor burden indicators for assessing LNM in T1 ESCC. Methods A retrospective analysis was conducted on clinical data and CT imaging of 243 patients with histologically confirmed T1 ESCC who underwent radical surgery. Cross-sectional areas of skeletal muscle, subcutaneous fat, and visceral fat at the level of the L3 vertebra were quantified using ImageJ software. Univariate and multivariate analyses were conducted to identify risk factors associated with LNM. A predictive nomogram was then constructed based on the multivariate results and evaluated using receiver operating characteristic (ROC) curves, calibration plots, and decision curve analysis (DCA). Results Among the 243 patients, 38 cases exhibited LNM, yielding an incidence rate of 15.64%. Multivariate analysis identified tumor size, lymphovascular invasion (LVI), visceral fat area (VFA), and T1 substage as independent risk factors. The AUC values for size, LVI, VFA, and T1 substage were 0.628, 0.651, 0.767, and 0.619, respectively. The nomogram constructed based on these four variables demonstrated strong predictive performance, with AUCs of 0.8331 in the training set and 0.8343 in the validation set, both surpassing the predictive capacity of individual indicators. These findings underscore the nomogram’s superior prognostic accuracy compared to any single pathological parameter. The calibration curve and DCA demonstrated its considerable potential for clinical application. Conclusion This nomogram, integrating body composition and tumor burden indicators, provides an individualized and practical tool for predicting LNM in early ESCC, supporting more informed clinical decision-making.